Developing E-Mowara: An archipelago-insighted electronic module to train middle school students' computational thinking skills - Nisa’, Thoiffatul Khusnun; Tazkia, Savirra; Fildzah, Natasya Nurhusnina; Palupi, Evangelista Lus Windyana (Jurnal Gantang, 2024)
To face the challenges of Indonesian education in the 21st century, the requirements for abilities are crucial, but the facts show that students are less able to use and adapt their abilities with insights aligned with the identity of the Indonesian nation. For this reason, researchers developed an E-Mowara: Interactive Emodule with an Archipelagic Outlook. This study aimed to develop the E-Mowara electronic module and find out students' responses after using the developed media. The target of this study was class VIII junior high school students with number pattern material. This development research uses a design research type of development study. The data collection technique in this study used a questionnaire with data processing techniques analyzed using percentage data analysis techniques. This is based on the validation results in terms of the material average of 84.35% with the appropriate criteria, and in terms of media, an average of 85.90% with the appropriate criteria. Students' responses to E-Mowara were quite good, with a percentage of 92.5%. Based on this result, the E-Mowara Electronic Module is known as valid, easy to use, and effective in developing computational thinking skills with insights that are in harmony with the identity of the Indonesian nation.